Contribution of Characteristics of Panchayat Leaders Towards Their Attitude as Evident from the Multiple Regression Analysis (Indian Journal of Extension Education, 2021)
The function of extension is to transfer and nurture the pool of knowledge within the rural system. Agricultural development however is often seen as an increase in agricultural production and/or the productivity of land, labour and capital in agriculture. The type of political leadership and individuals in power influences the rate and direction of change. The 73rd Amendment provides for an elaborate system of establishing Panchayats as units of self-government. Attitude is a learned pre disposition to react consistently in a given manner (either positively or negatively) to certain persons, objects or concepts. The interview schedule was used as a tool for collecting the raw information from the Panchayat leaders. In all 263 respondents from 9 janpads were interviewed personally to obtain the requisite data. Multiple regression analysis was done to know the combined effect of all the independent variables in explaining the variation on the dependent variables. Three independent variables viz. social participation, extension participation and role performance were observed to have positive and significant contribution in attitude of gram Panchayat leaders towards Panchayati raj institutions at 0.01 level of probability. The variables achievement motivation, cosmopoliteness and political affiliation had positive and significant contribution towards attitude of janpad and jila panchayat leaders at 0.01 level of probability